Perbandingan Kelimpahan Bakteri Asam Laktat Kandidat Probiotik pada Produk Susu dari Peternakan Sapi di Enrekang - Ega Delva; Tamina Melindah; Achintya A, Ni Ny Wedarthani; Diah Astini Paramita; M Hanif Addienda (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Enrekang Regency is the main producer of milk in South Sulawesi, offering significant potential for developing probiotic products based on indigenous lactic acid bacteria (LAB). This study aimed to analyze bacterial cell density in three types of Enrekang milk samples (fresh, pasteurized, and dangke waste) using Nutrient Agar (NA) and de Man, Rogosa, and Sharpe Agar (MRSA) media, and to characterize the macroscopic and microscopic morphology of LAB isolates. Results showed that bacterial density on NA medium ranged from 2.685 × 10⁸ to 5.596 × 10⁹ CFU/mL, with no significant differences among samples (F = 6.525; p = 0.081). In contrast, MRSA medium revealed highly significant differences (F = 615.789; p = 0.000), with pasteurized milk showing the highest density (1.633 × 10⁹ CFU/mL). Eleven LAB isolates (P1–P11) from pasteurized milk displayed uniform macroscopic characteristics. Microscopically, all isolates were Gram-positive, comprising cocci and coccobacilli with variable chain arrangements. These findings indicate the presence of indigenous LAB with promising potential as probiotic candidates or starter cultures and provide a basis for further biotechnological development and functional characterization.